2021
DOI: 10.1111/tmi.13546
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal carriage among Hajj pilgrims, risk factors for carriage and records of vaccination: a study of pilgrims to Mecca

Abstract: Objective The Saudi government requires that all pilgrims receive a quadrivalent meningococcal vaccine at least 10 days before the Hajj. We conducted a study to determine the uptake of meningococcal vaccine and antibiotic use. We also investigated risk factors of meningococcal carriage and carriage of Neisseria meningitidis pathogenic serogroups A, C, W and Y. Methods A cross‐sectional oropharyngeal carriage survey was conducted in 2973 Hajj pilgrims in September 2017. A real‐time polymerase chain reaction (rt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Results from a recent meta-analysis (spanning 2012–2017) indicate that N. meningitidis accounts for 9% and 36% of all bacterial meningitis cases in Eastern Mediterranean and African regions, respectively [ 108 ]. Furthermore, the burden of IMD in the Eastern Mediterranean Regional Office (EMRO) region is second highest after the African meningitis belt (bacterial meningitis is also second highest in the EMRO region compared with the African region), with several countries (where data exists) reporting moderate/high endemic rates [ 45 , 109 , 110 ]. In our review, the most comprehensive IMD incidence data were available for Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from a recent meta-analysis (spanning 2012–2017) indicate that N. meningitidis accounts for 9% and 36% of all bacterial meningitis cases in Eastern Mediterranean and African regions, respectively [ 108 ]. Furthermore, the burden of IMD in the Eastern Mediterranean Regional Office (EMRO) region is second highest after the African meningitis belt (bacterial meningitis is also second highest in the EMRO region compared with the African region), with several countries (where data exists) reporting moderate/high endemic rates [ 45 , 109 , 110 ]. In our review, the most comprehensive IMD incidence data were available for Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…Adults (18–> 65 y): 1.3 IIIb. All: 1.3 - B: 1.3 Saudi Arabia [ 40 ] Cross-sectional study King Abdul Aziz International Airport, King Khalid International Airport, camping (Jeddah Riyadh, Mina) Pilgrims N = 715 (before Hajj) N = 745 (post Hajj) Hajj study Before Hajj 2000: 8.0 Before Hajj 2000 Adults (18–100 y): 8.0 Before Hajj 2000 All: 8.0 - A: 0.4 - B: 1.3 - W135: 0.4 - Y: 0.6 - Other: 5.2 Post Hajj 2000: 10.4 Post Hajj 2000 Adults (18–100 y): 10.4 Post Hajj 2000: 10.4 - A: 0.0 - B: 0.4 - W135: 4.6 - Y: 0.0 - Other: 5.2 Saudi Arabia [ 41 ] Longitudinal study King Abdul-Aziz International Airport (Jeddah) Pilgrims Umra visitors N = 979 (before Umra) N = 979 (post Umra) Hajj N = 1433 (before Hajj) N = 613 (post Hajj) Hajj study Before Umra 2008: 2.5 Before Umra 2008 Adults (18–100 y): 2.5 Before Umra 2008 All: 2.5 Post Umra 2008: 5.7 Post Umra 2008 Adults (18–100 y): 5.7 Post Umra 2008 All: 5.7 Before Umra 2008: 5.9 Before Umra 2008 Adults (18–100 y): 5.9 Before Umra 2008 All: 5.9 Post Hajj 2008: 11.1 Post Hajj 2008 Adults (18–100 y): 11.1 Post Hajj 2008 All: 11.1 Saudi Arabia [ 45 ] Cross-sectional study Hajj terminal of King Abdulaziz International Airport (Jeddah) Pilgrims N = 2249 (post Hajj) Hajj study Post-Hajj 2017: 4.6 Children and adults (11–100 y): 4.6 All: 4.6 - A: 0.1 - B: 0.4 - C: 0.4 - W135: 0.1 - X: 0.3 - Y: 0.1 ...…”
Section: Objective 1: Asymptomatic Meningococcal Carriagementioning
confidence: 99%
See 1 more Smart Citation
“…In their 2014 study (published in 2017), Memish et al reported that 98.2% of the 1055 arriving pilgrims (most from countries we also describe below) had received the polysaccharide vaccine, and the remainder had received a conjugate vaccine [31]. A more recent 2017 study (published in 2021) involving 2973 pilgrims arriving from a wide range of countries reported that between 60 and 70% of vaccinated pilgrims arriving from low-and middle-income countries (LIMCs) had received polysaccharide MenACWY vaccine [32]. Perhaps more worrying was the high proportion of unvaccinated pilgrims from LIMCs (20-25%) [32].…”
Section: Imd Hajj Outbreaks and Subsequent Immunization Policymentioning
confidence: 95%
“…A recent study with detailed breakdown on vaccination history has shown that, even among overseas pilgrims, the actual vaccine uptake is only 77%. At least 11% of vaccination certificates are fake and another 12.6% are dubious; in 0.5%, an incorrect vaccine (e.g., bivalent vaccine) is recorded, making the certificate non-valid [ 18 ]. Suboptimal vaccination rates have also been reported among HCWs at Hajj [ 19 , 20 ].…”
mentioning
confidence: 99%